Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.jsxm.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Early Effect of Bariatric Surgery on Urogenital Function in Morbidly Obese Men

Abstract: Running head: Early effect of bariatric surgery on ED and LUTSKeywords: bariatric surgery, weight loss, erectile dysfunction, lower urinary tract symptoms, body mass index 2 Abstract:Introduction: Obesity is an independent risk factor for erectile dysfunction (ED) and lower urinary tract symptoms (LUTS). Bariatric surgery has been shown to improve erectile function and urinary symptoms in previous medium to long term studies (3-12 months post-operative follow up).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 39 publications
(36 reference statements)
1
33
0
1
Order By: Relevance
“…The meta-analysis results indicate that bariatric surgery presents conspicuously effective improvements on male's sexual function by comparing IIEF scores, including erectile function, intercourse satisfaction, overall satisfaction, orgasmic function, sexual desire, total erectile function and BSFI scores, including erection, ejaculation, problem assessment, sexual satisfaction. According to Aleid et al [29], the male's sexual function improvements caused by bariatric surgery resulting in increasing all the IIEF domains, which agree with the study performed by Efthymious et al [14] and other researches [24,26,27]. In contrast, studies undertook by Ranasinghe et al [25]and Sarwer et al [11], which also used IIEF to detect male's sexual function, found no effective improvements reaching statistically significance among obese man undergoing bariatric surgery.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The meta-analysis results indicate that bariatric surgery presents conspicuously effective improvements on male's sexual function by comparing IIEF scores, including erectile function, intercourse satisfaction, overall satisfaction, orgasmic function, sexual desire, total erectile function and BSFI scores, including erection, ejaculation, problem assessment, sexual satisfaction. According to Aleid et al [29], the male's sexual function improvements caused by bariatric surgery resulting in increasing all the IIEF domains, which agree with the study performed by Efthymious et al [14] and other researches [24,26,27]. In contrast, studies undertook by Ranasinghe et al [25]and Sarwer et al [11], which also used IIEF to detect male's sexual function, found no effective improvements reaching statistically significance among obese man undergoing bariatric surgery.…”
Section: Discussionsupporting
confidence: 62%
“…Meanwhile, the main finding of the prospective study, performed by Efthymious et al [14], was that the bariatric surgery could lead to a significant improvement in sexual functioning and especially could be find in the first 6 months postoperatively. In a prospective study of bariatric surgery, which used the IIEF score respectively, Aleid et al [29]. similarly find significant improvements in male erectile function.…”
Section: Results Of Each Studymentioning
confidence: 96%
See 1 more Smart Citation
“…Грызуны с ожирением, которых кормят пищей с повышенным содержанием жиров, являются наиболее часто применяемой лабораторной моделью для ЭД [9]. Существуют указания на то, что бариатрическая хирургия приводит к уменьшению выраженности ЭД [10,11].…”
Section: научный обзорunclassified
“…A 14-year prospective study identified obesity as a risk factor for erectile dysfunction [ 14 ] and a 12-week HF diet decreased erectile function in rats [ 15 ]. Moreover, weight reduction with bariatric surgery improved erectile dysfunction significantly in obese men [ 16 ]. Recently, Moon et al [ 17 ] reported that daily administration of udenafil (75 mg/d) for 6 months improved erectile dysfunction in a randomized placebo-controlled clinical trial.…”
Section: Introductionmentioning
confidence: 99%